If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 1y = 67 Solving 6x + 1y = 67 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 6x + 1y + -1y = 67 + -1y Combine like terms: 1y + -1y = 0 6x + 0 = 67 + -1y 6x = 67 + -1y Divide each side by '6'. x = 11.16666667 + -0.1666666667y Simplifying x = 11.16666667 + -0.1666666667y
| 0.2(x-25.5)+.3=-.2(x-16) | | 92-(4x+11)=4(x+9)+x | | 21.12=5.5p-5.4+7.6 | | (5w-5g)(5w+4g)= | | 36+-17+-11= | | 18-2g=48 | | 40x+32=472 | | y=x^2+0x-64 | | 2X^2+8X+Y^2-4Y=24 | | 3x+6=15x | | .2(x-255)+.3=-.2(x-16) | | 5x+x+2x=80 | | 64x=1088 | | (2/5)x+1-(5/3)x=(41/60) | | C=rd | | -3x+9=9-3x | | y=5x^2+45x+70 | | 7x=59-(13x-21) | | x+2x+3x=20 | | -2=x+(4/5)-2x | | 13u-8u=45 | | 1.8+x-3.8=-4+5.9 | | 3x^3+2x^2-3x-2=0 | | 90-5x=35 | | 5x+20=2x+26 | | 7-5x=10+(6x+7) | | 4(x-6)=56-6x | | mx^2+2x-m=m-x | | 90-5x=354 | | -16.128=2.1r+1.74r | | 3x-8=52-9x | | (2/3)x-(4/3)x=(2/3) |